(untitled) (Journal of Economic Research & Business Administration, 2016)
The purpose of this article is to examine the use of instruments of public-private partnerships to improve the energy efficiency of the Repub- lic of Kazakhstan. They focus on exploring the possibilities of using instru- ments of public-private partnerships to improve the energy efficiency of the Republic of Kazakhstan, which makes it possible to greatly intensify the activities of private enterprises in this field. It also discusses the meth- odological aspects of the issue, as well as the possibility of using bench- marking to build an effective system of energy audit.To achieve this goal used methods of analysis of theoretical material, collection and processing of statistical data, work with the laws and regulations for the formation of specific recommendations. The analysis was prepared specific recommen- dations on selected topics. All the conclusions presented in the article have been formed in accordance with the main problematic issues of the article.